Direct observation of carrier accumulation at the PbSe colloidal quantum Dot/ZnO interface. (15th March 2022) - Park, Byoungnam
Abstract: For the first time, we quantified the ZnO/lead sulfide (PbSe) contact resistance directly using a ZnO/PbSe/ZnO test platform, eliminating the additional interface associated with metal electrodes which complicate the direct analysis of the contact properties. We demonstrated that a significant enhancement of the interfacial charge transfer rate through the ligand removal process of the PbSe colloid quantum dots (CQDs) with ammonium sulfide ((NH4 )2 S) treatment results from the accumulation of mobile carriers. The ligand removal process dramatically decreased the contact resistivity from 1.0ⅹ10 3 (after 1, 2-ethanedithiol (EDT)-treatment) to 7.9 Ω cm 2 . A significant increase in the carrier concentration was observed in the ZnO/PbSe contact region as well as the PbSe CQD channel, mitigating carrier depletion at the contact. We propose that the ligand removal process led to thermally-activated hopping of carriers from the ZnO to the PbSe instead of trap-assisted tunneling in the EDT-treated PbSe CQDs.